Bargaining with a Heterogeneous Player: An Application to the GATT Uruguay Round - Girogio Basevi; Flavio Delbono; Marco Mariotti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
This paper was written while the first author was visiting professor at the Department of Economics , birkbeck College, University of London. We are indebted to Alison Booth and Steve Davies for useful suggestions in reffering us to models used in literature on trade unions. The paper is part of research, and by the Italian Ministry for University and Scientific Research Council (C.N.R.)
Keywords: 330